1985
DOI: 10.1002/1097-0142(19851015)56:8<2019::aid-cncr2820560822>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous estrogen receptor levels detected via multiple microsamples from individual breast cancers

Abstract: Twenty-six surgical breast cancer specimens were subjected to multiple estrogen receptor (ER) assays with a microsample technique. In most tumors there were large variations in ER Levels in samples taken from different regions of the same tumor. After correction of individual samples for differences in carcinoma content, such variations were not abolished. Nine of the 26 breast cancers, although positive overall, were devoid of ER in some regions. For ER-positive tumors the average coefficient of variation (CV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
7
0
2

Year Published

1986
1986
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 22 publications
3
7
0
2
Order By: Relevance
“…Interestingly, our results indicated that an extensive variance in 18 F-FES uptake can be present across positive lesions within individuals (coefficient of variance, 68% 6 4%). This heterogeneity matches findings of multiple biopsies from individual patients showing that a variety of ER levels can be present (30,31). Furthermore, 45% of the patients with a positive 18 F-FES PET finding had both 18 F-FES-positive and 18 F-FES-negative metastases.…”
Section: Discussionsupporting
confidence: 82%
“…Interestingly, our results indicated that an extensive variance in 18 F-FES uptake can be present across positive lesions within individuals (coefficient of variance, 68% 6 4%). This heterogeneity matches findings of multiple biopsies from individual patients showing that a variety of ER levels can be present (30,31). Furthermore, 45% of the patients with a positive 18 F-FES PET finding had both 18 F-FES-positive and 18 F-FES-negative metastases.…”
Section: Discussionsupporting
confidence: 82%
“…These antigens were chosen, in part because they are routinely performed on diagnostic specimens, and also because their expression from place to place within individual breast cancers is regarded as significantly heterogeneous. (Brennan et al, 1979;Layfield et al, 1998;Rosen et al, 1977;van Netten et al, 1985). In our cohort the percentage of ER-, PR-, and HER2-positive cases, based on whole-section staining, was 68%, 56%, and 24%, respectively.…”
Section: Resultsmentioning
confidence: 57%
“…On a more speculative note, it is possible that expression in the majority of cells is suppressed by dominant cells expressing high levels of the protein. Heterogeneity of oestrogen receptor levels has been demonstrated biochemically in different areas of the same tumour (van Netten et al, 1985) and immunohistochemically, in different cells (King et al, 1985). Immunohistochemical staining of other oestrogen-regulated proteins such as progesterone receptor (Soomro & Shousha, 1990) pNR-2 immunohistochemical staining was significantly associated with positive oestrogen receptor status (defined by a 5 fmol mg-' cytosolic protein threshold in a dextran coated charcoal ligand binding assay).…”
Section: Discussionmentioning
confidence: 99%